2012
DOI: 10.1103/physreva.85.034504
|View full text |Cite
|
Sign up to set email alerts
|

Protonic structure of CH3OH described by electroprotonic wave functions

Abstract: The electroprotonic ground-state wave function of CH 3 OH is calculated beyond the Born-Oppenheimer (BO) approximation using multiconfiguration wave-function theory for a system composed of electrons and protons. A CH 3 OH molecule is treated as a quasidiatomic molecule in which orbitals for both electrons and protons are described in a laboratory fixed cylindrical coordinate system with C and O atoms being fixed on the z axis. The probability density of the four protons shows that the C atom is surrounded by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Most recently, it was demonstrated that the proton density in methanol obtained from an electronproton orbital computation (with fixed carbon and oxygen nuclei) can be matched with the spatial configuration obtained from a BO electron-structure calculation [84]. Furthermore, in addition to the electronic and nuclear densities, flux densities have also been considered in Refs.…”
Section: A Probabilistic Interpretation Of the Wave Functionmentioning
confidence: 99%
“…Most recently, it was demonstrated that the proton density in methanol obtained from an electronproton orbital computation (with fixed carbon and oxygen nuclei) can be matched with the spatial configuration obtained from a BO electron-structure calculation [84]. Furthermore, in addition to the electronic and nuclear densities, flux densities have also been considered in Refs.…”
Section: A Probabilistic Interpretation Of the Wave Functionmentioning
confidence: 99%
“…The ideas presented here can also be extended to other derived theories emanating from the MCTDH theory, such that for mixtures of identical particles [87,88], also see Refs. [89,90]. The separation of the coefficients, which define the reduced density matrices, from the orbitals [79] suggests that other representations for the time-dependent manybody wavepackets would be amenable to linear response in the spirit presented here.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…The migration, exchange, and scrambling processes of protons occurring within a very short period of time (B40 fs) may be a general phenomenon when hydrocarbon molecules are exposed to an intense laser field, and this highly correlated dynamics of protons (deuterons) may require a representation of protons as multiple-centered wave functions like those introduced recently by our group. 18,19…”
Section: Comparison Between I and I A And Between Ii And Ii Amentioning
confidence: 99%